Estratégias alternativas de produção no cinema brasileiro contemporâneo: o caso da cooperativa Filmes a granel - Rolim , Cristhine Lucena (2017)
In the midst of both technological evolution and democratization of the means for audiovisual production within the 21st century, we are experiencing a moment of effervescence in Cinema with new possibilities for independent film-making through the creative employment of digital technologies. Both the attempt at finding alternative strategies in Brazilian cinema and the arising of novel models for audiovisual production provide an advantageous field for academic studies on social and economic contexts and ways of organization within film-making. I intend to reflect about the recent production process in the Brazilian cinema by observing experiences that seek for solutions that are different from the hegemonic industrial model and that appear as a cornerstone for cinema in the digital era. The study here presented considers the following elements as a tripod for audiovisual production: equipaments, funding, and the team. I suggest that the technical, the economic, and the affective fields are crucial for understanding the above mentioned elements within independent cinema. Within this scenario, the thesis examines modes of production in contemporary cinema by taking the model undertaken by Cooperativa Filmes a Granel from Paraíba state - which is part of what we call the Digital Phase of cinema in Paraíba - as a case study.